Uplift Performance of Plate Anchors in Cement-Stabilised Aeolian Sand - Qian, Zengzhen; Sheng, Mingqiang; Huang, Faming; Lu, Xianlong (Frontiers in Earth Science, 2021)
Comparative pullout tests were carried out on model plate anchors in uncemented aeolian sand (UAS) and cement-stabilised aeolian sand (CAS) with different embedment ratios of the embedment depth (H) to the width (D) of the plate to examine the effectiveness of the insertion of cement in aeolian sand to enhance the uplift performance of plate anchors. Experimental results demonstrated that significant increases in failure resistance and uplift stiffness can be achieved, irrespective of embedment ratios of H/D, when a relatively small amount of cement (an optimal cement content of 6% by weight of dry aeolian sand determined by direct shear test in this study) was added to the aeolian sand backfill. However, distinct load–displacement responses were observed in all the tests on the model plate anchors embedded in CAS and UAS backfills: two-phase of pre-peak and post-peak behaviour in CAS and three-phase of initial linear, nonlinear transition to peak uplift resistance, and post-peak behaviour in UAS; failure of the former started at tiny displacements and that of the latter appeared at large displacements. Therefore, the significant increases in uplift failure resistance and pre-peak uplift stiffness were limited to relatively low uplift displacements because of the brittle nature of the improved CAS backfills shear strength characteristics.